Bandrek Cappuccino-Based Pudding Innovation - Rika Yuliyani; Siti Zakiah (Publikasi Indonesia, 2024)
This research was motivated by the limited product differentiation of bandrek cappuccino. The purpose of the research was to develop an innovative product “Bacino Bandrek Cappuccino Pudding” by making a recipe formulation and analyzing the sensory characteristics (taste, aroma, and texture) and formulating the recipe formulation. The method used was experimental analysis through sensory testing and recipe development. The results showed that the product innovation “Bacino Bandrek Cappuccino Pudding” has unique sensory characteristics and is acceptable to consumers. The recipe formulation developed also succeeded in producing a consistent product. It is hoped that cappuccino sellers in the city market can adopt this product innovation to increase their competitiveness and income. Further research is needed to gauge the level of market acceptance and effective marketing strategies